Integration of Technology and Islamic Education in the Digital Era: Challenges, Opportunities and Strategies - Mar, Nur Azaliah (Science Tech Group, 2024)
This literature study describes various important aspects of technology integration and Islamic education in the digital era. First, the integration of technology in learning shows educators' high confidence in the benefits of technology to improve the teaching process, although there are concerns regarding infrastructure and student readiness. Second, studies on the challenges of Islamic education in the digital era highlight the spread of misinformation and the negative impact of social media, which can be addressed by strengthening digital literacy and the integration of Islamic values ​​in the curriculum. The role of social media in Muslim society is found to be beneficial for spreading religious teachings, but it also has moral risks if it is not used wisely in accordance with religious values. The transformation of Islamic boarding schools in this disruptive era requires the adaptation of modern technology in teaching traditional Islamic values ​​such as tarbiyah, ta'lim, and ta'dib. Integration of science and Al-Qur’an in Islamic universities identifies the challenge of coordinating the integration vision throughout the university with its implementation at lower levels. This study provides insight for stakeholders to strengthen Islamic education in the digital era with an approach that meets the demands of the times, while maintaining classical religious values.